2017
DOI: 10.1016/j.evolhumbehav.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Aggressor or protector? Experiences and perceptions of violence predict preferences for masculinity

Abstract: Women's preferences for masculine male partners have been explained in terms of heritable health. The evidence between masculinity and health, however, is controversial and therefore, alternative explanations for masculinity preferences reflecting income inequality and protection from violence have been proposed. This study thus aimed to test the effect of exposure to violence (i.e., experiences of robberies and perceptions of danger) on the individual masculinity preferences of women and men from the capital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 48 publications
3
57
0
Order By: Relevance
“…The other independent influence on masculinity preferences our study did not investigate is perceived threat of violence and/or sexual coercion. Two recent studies found that women's masculinity preferences decrease when primed with images of male-on-female aggression (Li et al 2014) or when exposed to higher levels of violence (Borras-Guevara et al 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other independent influence on masculinity preferences our study did not investigate is perceived threat of violence and/or sexual coercion. Two recent studies found that women's masculinity preferences decrease when primed with images of male-on-female aggression (Li et al 2014) or when exposed to higher levels of violence (Borras-Guevara et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, it has been found that masculine facial traits increase both perceived dominance and negative attributions of male faces including decreased quality as a parent (e.g., Boothroyd et al 2007;Borras-Guevara et al 2017;Penton-Voak et al 1999;Perrett et al 1998). Indeed, high levels of testosterone have been linked to undesirable social traits such as aggression and decreased paternal investment (e.g., Booth and Dabbs 1993;Mascaro et al 2013;Pollet et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This lies in contrast to the priming of increased masculinity preferences when women were are shown men’s aggression towards men (Li et al 2014 ). Additionally, Colombian women who agreed with the statement “men are dangerous to their children” had low masculinity preferences for male faces (Borras-Guevara et al 2017 ). Following the trade-off theory, the above literature suggests that the violence source coming either from strangers (public violence) or from partners (domestic violence), could have different effects on women’s masculinity preferences, since the types of violence could be associated with different costs and benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings have suggested that experiencing violence may have an impact on women’s choices regarding male facial masculinity [ 51 , 52 , 53 ]. By using a well-validated methodology [ 22 , 44 ], we have explored the association between a history of sexual/physical abuse with the choice of hypothetical male partners for short- and long-term relationships.…”
Section: Discussionmentioning
confidence: 99%